Intelligent control of robotic systems - Behera, Laxmidhar (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"The book illustrates basic principles along with the development of the advanced algorithms to realize smart robotic systems. It talks about strategies by which a robot (manipulators, mobile robot, quadrotor) can learn its own kinematics and dynamics from data. In this context, two major issues have been dealt with namely stability of the systems and experimental validations. Learning algorithms and techniques as covered in this book easily extend to other robotic systems as well. The book contains MATLAB based examples and c-codes under robot operating systems (ROS) for experimental validation so that readers can replicate these algorithms in robotics platforms"--
OCLC-licensed vendor bibliographic record.
Keywords: Robots -- Control systems; Intelligent control systems; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Robotics